Sex-specific accumulated oxygen deficit during short- and middle-distance swimming performance in competitive youth athletes. - Massini, D. A.; Almeida, T. A. F.; Macedo, A. G.; Espada, M. C.; Reis, J. F.; Alves, F. J. B.; Fernandes, R. J. P.; Filho, D. M. P. (Sports Medicine - Open, 2023)
Key Points